English Vocabulary Learning among First Year Non-English Major Students: A Cross-sectional Study at a Private University in Vietnam (Journal of Contemporary Educational Policies and Practices, 2025)
Learning a language inherently involves acquiring its vocabulary. However, developing a comprehensive vocabulary is a significant challenge for many language learners. This study aimed to assess the current situation and students' awareness of English vocabulary learning among first year non-English majors at Thanh Do University, Vietnam. A cross-sectional descriptive study was conducted with 347 students from five departments (Information Technology, Automotive Engineering Technology, Electrical and Electronic Engineering Technology, Economics and Law, and Pharmacy) from September to November 2024. The results revealed that 89.63% of the respondents recognized the importance of vocabulary, with 53.60% viewing it as “very necessary”. Despite this awareness, the students faced significant challenges in retaining and applying vocabulary in practical contexts. The primary barriers identified comprised lack of motivation (67.72%), limited study time (63.41%), and ineffective learning methods (e.g., rote memorization, used by 66.33% of students). Only 28.74% of students were motivated to improve their communication skills, with the majority (63.22%) focusing on enhancing academic performance. Additionally, 80.69% reported difficulty with long-term vocabulary retention, while 76.37% struggled with pronunciation. To address these issues, the researchers propose practical solutions such as diversifying teaching methods, incorporating modern learning tools, and creating more language practice environments both in and outside the classroom. These strategies aim to enhance vocabulary retention, application, and overall English proficiency, ultimately helping students meet academic and professional demands.